Age-sex differences in the global burden of lower respiratory infections and risk factors, 1990-2019: results from the Global Burden of Disease Study 2019 - Kyu, Hmwe Hmwe; Jonas, Jost B. (The lancet. Infectious diseases, 2022)
Background - The global burden of lower respiratory infections (LRIs) and corresponding risk factors in children older than 5 years and adults has not been studied as comprehensively as it has been in children younger than 5 years. We assessed the burden and trends of LRIs and risk factors across all age groups by sex, for 204 countries and territories. - Methods - In this analysis of data for the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019, we used clinician-diagnosed pneumonia or bronchiolitis as our case definition for LRIs. We included International Classification of Diseases 9th edition codes 079.6, 466-469, 470.0, 480-482.8, 483.0-483.9, 484.1-484.2, 484.6-484.7, and 487-489 and International Classification of Diseases 10th edition codes A48.1, A70, B97.4-B97.6, J09-J15.8, J16-J16.9, J20-J21.9, J91.0, P23.0-P23.4, and U04-U04.9. We used the Cause of Death Ensemble modelling strategy to analyse 23 109 site-years of vital registration data, 825 site-years of sample vital registration data, 1766 site-years of verbal autopsy data, and 681 site-years of mortality surveillance data. We used DisMod-MR 2.1, a Bayesian meta-regression tool, to analyse age-sex-specific incidence and prevalence data identified via systematic reviews of the literature, population-based survey data, and claims and inpatient data. Additionally, we estimated age-sex-specific LRI mortality that is attributable to the independent effects of 14 risk factors. - Findings - Globally, in 2019, we estimated that there were 257 million (95% uncertainty interval [UI] 240-275) LRI incident episodes in males and 232 million (217-248) in females. In the same year, LRIs accounted for 1·30 million (95% UI 1·18-1·42) male deaths and 1·20 million (1·07-1·33) female deaths. Age-standardised incidence and mortality rates were 1·17 times (95% UI 1·16-1·18) and 1·31 times (95% UI 1·23-1·41) greater in males than in females in 2019. Between 1990 and 2019, LRI incidence and mortality rates declined at different rates across age groups and an increase in LRI episodes and deaths was estimated among all adult age groups, with males aged 70 years and older having the highest increase in LRI episodes (126·0% [95% UI 121·4-131·1]) and deaths (100·0% [83·4-115·9]). During the same period, LRI episodes and deaths in children younger than 15 years were estimated to have decreased, and the greatest decline was observed for LRI deaths in males younger than 5 years (-70·7% [-77·2 to -61·8]). The leading risk factors for LRI mortality varied across age groups and sex. More than half of global LRI deaths in children younger than 5 years were attributable to child wasting (population attributable fraction [PAF] 53·0% [95% UI 37·7-61·8] in males and 56·4% [40·7-65·1] in females), and more than a quarter of LRI deaths among those aged 5-14 years were attributable to household air pollution (PAF 26·0% [95% UI 16·6-35·5] for males and PAF 25·8% [16·3-35·4] for females). PAFs of male LRI deaths attributed to smoking were 20·4% (95% UI 15·4-25·2) in those aged 15-49 years, 30·5% (24·1-36·9) in those aged 50-69 years, and 21·9% (16·8-27·3) in those aged 70 years and older. PAFs of female LRI deaths attributed to household air pollution were 21·1% (95% UI 14·5-27·9) in those aged 15-49 years and 18·2% (12·5-24·5) in those aged 50-69 years. For females aged 70 years and older, the leading risk factor, ambient particulate matter, was responsible for 11·7% (95% UI 8·2-15·8) of LRI deaths. - Interpretation - The patterns and progress in reducing the burden of LRIs and key risk factors for mortality varied across age groups and sexes. The progress seen in children younger than 5 years was clearly a result of targeted interventions, such as vaccination and reduction of exposure to risk factors. Similar interventions for other age groups could contribute to the achievement of multiple Sustainable Development Goals targets, including promoting wellbeing at all ages and reducing health inequalities. Interventions, including addressing risk factors such as child wasting, smoking, ambient particulate matter pollution, and household air pollution, would prevent deaths and reduce health disparities. - Funding - Bill & Melinda Gates Foundation.
Online verfügbar: 11. August 2022, Artikelversion: 26. Oktober 2022
Mitglieder der GBD 2019 LRI Collaborators: Hmwe Hmwe Kyu, Avina Vongpradith, Sarah Brooke Sirota, Amanda Novotney, Christopher E Troeger, Matthew C Doxey, Rose G Bender, Jorge R Ledesma, Molly H Biehl, Samuel B Albertson, Joseph Jon Frostad, Katrin Burkart, Fiona B Bennitt, Jeff T Zhao, William M Gardner, Hailey Hagins, Dana Bryazka, Regina-Mae Villanueva Dominguez, Semagn Mekonnen Abate, Michael Abdelmasseh, Amir Abdoli, Gholamreza Abdoli, Aidin Abedi, Vida Abedi, Tadesse M Abegaz, Hassan Abidi, Richard Gyan Aboagye, Hassan Abolhassani, Yonas Derso Abtew, Hiwa Abubaker Ali, Eman Abu-Gharbieh, Ahmed Abu-Zaid, Kidist Adamu, Isaac Yeboah Addo, Oyelola A Adegboye, Mohammad Adnan, Qorinah Estiningtyas Sakilah Adnani, Muhammad Sohail Afzal, Saira Afzal, Bright Opoku Ahinkorah, Aqeel Ahmad, Araz Ramazan Ahmad, Sajjad Ahmad, Ali Ahmadi, Sepideh Ahmadi, Haroon Ahmed, Jivan Qasim Ahmed, Tarik Ahmed Rashid, Mostafa Akbarzadeh-Khiavi, Hanadi Al Hamad, Luciana Albano, Mamoon A Aldeyab, Bezatu Mengistie Alemu, Kefyalew Addis Alene, Abdelazeem M Algammal, Fadwa Alhalaiqa Naji Alhalaiqa, Robert Kaba Alhassan, Beriwan Abdulqadir Ali, Liaqat Ali, Musa Mohammed Ali, Syed Shujait Ali, Yousef Alimohamadi, Vahid Alipour, Adel Al-Jumaily, Syed Mohamed Aljunid, Sami Almustanyir, Rajaa M Al-Raddadi, Rami H Hani Al-Rifai, Saif Aldeen S AlRyalat, Nelson Alvis-Guzman, Nelson J Alvis-Zakzuk, Edward Kwabena Ameyaw, Javad Javad Aminian Dehkordi, John H Amuasi, Dickson A Amugsi, Etsay Woldu Anbesu, Adnan Ansar, Anayochukwu Edward Anyasodor, Jalal Arabloo, Demelash Areda, Ayele Mamo Argaw, Zeleke Gebru Argaw, Judie Arulappan, Raphael Taiwo Aruleba, Mulusew A Asemahagn, Seyyed Shamsadin Athari, Daniel Atlaw, Engi F Attia, Sameh Attia, Avinash Aujayeb, Tewachew Awoke, Tegegn Mulatu Ayana, Martin Amogre Ayanore, Sina Azadnajafabad, Mohammadreza Azangou-Khyavy, Samad Azari, Amirhossein Azari Jafari, Muhammad Badar, Ashish D Badiye, Nayereh Baghcheghi, Sara Bagherieh, Atif Amin Baig, Maciej Banach, Indrajit Banerjee, Mainak Bardhan, Francesco Barone-Adesi, Hiba Jawdat Barqawi, Amadou Barrow, Azadeh Bashiri, Quique Bassat, Abdul-Monim Mohammad Batiha, Abate Bekele Belachew, Melaku Ashagrie Belete, Uzma Iqbal Belgaumi, Akshaya Srikanth Bhagavathula, Nikha Bhardwaj, Pankaj Bhardwaj, Parth Bhatt, Vijayalakshmi S Bhojaraja, Zulfiqar A Bhutta, Soumitra S Bhuyan, Ali Bijani, Saeid Bitaraf, Belay Boda Abule Bodicha, Nikolay Ivanovich Briko, Danilo Buonsenso, Muhammad Hammad Butt, Jiao Cai, Paulo Camargos, Luis Alberto Cámera, Promit Ananyo Chakraborty, Muluken Genetu Chanie, Jaykaran Charan, Vijay Kumar Chattu, Patrick R Ching, Sungchul Choi, Yuen Yu Chong, Sonali Gajanan Choudhari, Enayet Karim Chowdhury, Devasahayam J Christopher, Dinh-Toi Chu, Natalie L Cobb, Aaron J Cohen, Natália Cruz-Martins, Omid Dadras, Fentaw Teshome Dagnaw, Xiaochen Dai, Lalit Dandona, Rakhi Dandona, An Thi Minh Dao, Sisay Abebe Debela, Biniyam Demisse, Fitsum Wolde Demisse, Solomon Demissie, Diriba Dereje, Hardik Dineshbhai Desai, Abebaw Alemayehu Desta, Belay Desye, Sameer Dhingra, Nancy Diao, Daniel Diaz, Lankamo Ena Digesa, Linh Phuong Doan, Milad Dodangeh, Deepa Dongarwar, Fariba Dorostkar, Wendel Mombaque dos Santos, Haneil Larson Dsouza, Eleonora Dubljanin, Oyewole Christopher Durojaiye, Hisham Atan Edinur, Elham Ehsani-Chimeh, Ebrahim Eini, Michael Ekholuenetale, Temitope Cyrus Ekundayo, Eman D El Desouky, Iman El Sayed, Maysaa El Sayed Zaki, Muhammed Elhadi, Ahmed Mahmoud Rabie Elkhapery, Amir Emami, Luchuo Engelbert Bain, Ryenchindorj Erkhembayar, Farshid Etaee, Mohamad Ezati Asar, Adeniyi Francis Fagbamigbe, Shahab Falahi, Aida Fallahzadeh, Anwar Faraj, Emerito Jose A Faraon, Ali Fatehizadeh, Pietro Ferrara, Allegra Allegra Ferrari, Getahun Fetensa, Florian Fischer, Joanne Flavel, Masoud Foroutan, Peter Andras Gaal, Abhay Motiramji Gaidhane, Santosh Gaihre, Nasrin Galehdar, Alberto L Garcia-Basteiro, Tushar Garg, Mesfin Damtew Gebrehiwot, Mathewos Alemu Gebremichael, Yibeltal Yismaw Gela, Belete Negese Belete Gemeda, Bradford D Gessner, Melaku Getachew, Asmare Getie, Seyyed-Hadi Ghamari, Mohammad Ghasemi Nour, Ahmad Ghashghaee, Ali Gholamrezanezhad, Abdolmajid Gholizadeh, Rakesh Ghosh, Sherief Ghozy, Pouya Goleij, Mohamad Golitaleb, Giuseppe Gorini, Alessandra C Goulart, Girma Garedew Goyomsa, Habtamu Alganeh Guadie, Zewdie Gudisa, Rashid Abdi Guled, Sapna Gupta, Veer Bala Gupta, Vivek Kumar Gupta, Alemu Guta, Parham Habibzadeh, Arvin Haj-Mirzaian, Rabih Halwani, Samer Hamidi, Md Abdul Hannan, Mehdi Harorani, Ahmed I Hasaballah, Hamidreza Hasani, Abbas M Hassan, Shokoufeh Hassani, Hossein Hassanian-Moghaddam, Hadi Hassankhani, Khezar Hayat, Behzad Heibati, Mohammad Heidari, Demisu Zenbaba Heyi, Kamal Hezam, Ramesh Holla, Sung Hwi Hong, Nobuyuki Horita, Mohammad-Salar Hosseini, Mehdi Hosseinzadeh, Mihaela Hostiuc, Mowafa Househ, Soodabeh Hoveidamanesh, Junjie Huang, Nawfal R Hussein, Ivo Iavicoli, Segun Emmanuel Ibitoye, Kevin S Ikuta, Olayinka Stephen Ilesanmi, Irena M Ilic, Milena D Ilic, Mustapha Immurana, Nahlah Elkudssiah Ismail, Masao Iwagami, Jalil Jaafari, Elham Jamshidi, Sung-In Jang, Amirreza Javadi Mamaghani, Tahereh Javaheri, Fatemeh Javanmardi, Javad Javidnia, Sathish Kumar Jayapal, Umesh Jayarajah, Shubha Jayaram, Alelign Tasew Jema, Wonjeong Jeong, Jost B Jonas, Nitin Joseph, Farahnaz Joukar, Jacek Jerzy Jozwiak, Vaishali K, Zubair Kabir, Salah Eddine Oussama Kacimi, Vidya Kadashetti, Laleh R Kalankesh, Rohollah Kalhor, Ashwin Kamath, Bhushan Dattatray Kamble, Himal Kandel, Tesfaye K Kanko, Ibraheem M Karaye, André Karch, Samad Karkhah, Bekalu Getnet Kassa, Patrick DMC Katoto, Harkiran Kaur, Rimple Jeet Kaur, Leila Keikavoosi-Arani, Mohammad Keykhaei, Yousef Saleh Khader, Himanshu Khajuria, Ejaz Ahmad Khan, Gulfaraz Khan, Imteyaz A Khan, Maseer Khan, Md Nuruzzaman Khan, Moien AB Khan, Yusra H Khan, Moawiah Mohammad Khatatbeh, Mina Khosravifar, Jagdish Khubchandani, Min Seo Kim, Ruth W Kimokoti, Adnan Kisa, Sezer Kisa, Niranjan Kissoon, Luke D Knibbs, Sonali Kochhar, Farzad Kompani, Hamid Reza Koohestani, Vladimir Andreevich Korshunov, Soewarta Kosen, Parvaiz A Koul, Ai Koyanagi, Kewal Krishan, Barthelemy Kuate Defo, G Anil Kumar, Om P Kurmi, Ambily Kuttikkattu, Dharmesh Kumar Lal, Judit Lám, Iván Landires, Caterina Ledda, Sang-woong Lee, Miriam Levi, Sonia Lewycka, Gang Liu, Wei Liu, Rakesh Lodha, László Lorenzovici, Mojgan Lotfi, Joana A Loureiro, Farzan Madadizadeh, Ata Mahmoodpoor, Razzagh Mahmoudi, Marzieh Mahmoudimanesh, Jamal Majidpoor, Alaa Makki, Elaheh Malakan Rad, Ahmad Azam Malik, Tauqeer Hussain Mallhi, Yosef Manla, Clara N Matei, Alexander G Mathioudakis, Richard James Maude, Entezar Mehrabi Nasab, Addisu Melese, Ziad A Memish, Oliver Mendoza-Cano, Alexios-Fotios A Mentis, Tuomo J Meretoja, Mehari Woldemariam Merid, Tomislav Mestrovic, Ana Carolina Micheletti Gomide Nogueira de Sá, Gelana Fekadu Worku Mijena, Le Huu Nhat Minh, Shabir Ahmad Mir, Reza Mirfakhraie, Seyyedmohammadsadeq Mirmoeeni, Agha Zeeshan Mirza, Moonis Mirza, Mohammad Mirza-Aghazadeh-Attari, Abay Sisay Misganaw, Awoke Temesgen Misganaw, Esmaeil Mohammadi, Mokhtar Mohammadi, Arif Mohammed, Shafiu Mohammed, Syam Mohan, Mohammad Mohseni, Nagabhishek Moka, Ali H Mokdad, Sara Momtazmanesh, Lorenzo Monasta, Md Moniruzzaman, Fateme Montazeri, Catrin E Moore, Abdolvahab Moradi, Lidia Morawska, Jonathan F Mosser, Ebrahim Mostafavi, Majid Motaghinejad, Haleh Mousavi Isfahani, Seyed Ali Mousavi-Aghdas, Sumaira Mubarik, Efrén Murillo-Zamora, Ghulam Mustafa, Sanjeev Nair, Tapas Sadasivan Nair, Houshang Najafi, Atta Abbas Naqvi, Sreenivas Narasimha Swamy, Zuhair S Natto, Biswa Prakash Nayak, Seyed Aria Nejadghaderi, Huy Van Nguyen Nguyen, Robina Khan Niazi, Antonio Tolentino Nogueira de Sá, Hasti Nouraei, Ali Nowroozi, Virginia Nuñez-Samudio, Chimezie Igwegbe Nzoputam, Ogochukwu Janet Nzoputam, Bogdan Oancea, Chimedsuren Ochir, Oluwakemi Ololade Odukoya, Hassan Okati-Aliabad, Akinkunmi Paul Okekunle, Osaretin Christabel Okonji, Andrew T Olagunju, Isaac Iyinoluwa Olufadewa, Ahmed Omar Bali, Emad Omer, Eyal Oren, Erika Ota, Nikita Otstavnov, Abderrahim Oulhaj, Mahesh P a, Jagadish Rao Padubidri, Keyvan Pakshir, Reza Pakzad, Tamás Palicz, Anamika Pandey, Suman Pant, Shahina Pardhan, Eun-Cheol Park, Eun-Kee Park, Fatemeh Pashazadeh Kan, Rajan Paudel, Shrikant Pawar, Minjin Peng, Gavin Pereira, Simone Perna, Navaraj Perumalsamy, Ionela-Roxana Petcu, David M Pigott, Zahra Zahid Piracha, Vivek Podder, Roman V Polibin, Maarten J Postma, Hamid Pourasghari, Naeimeh Pourtaheri, Mirza Muhammad Fahd Qadir, Mathieu Raad, Mohammad Rabiee, Navid Rabiee, Saber Raeghi, Alireza Rafiei, Fakher Rahim, Mehran Rahimi, Vafa Rahimi-Movaghar, Azizur Rahman, Md Obaidur Rahman, Mosiur Rahman, Muhammad Aziz Rahman, Amir Masoud Rahmani, Vahid Rahmanian, Pradhum Ram, Kiana Ramezanzadeh, Juwel Rana, Priyanga Ranasinghe, Usha Rani, Sowmya J Rao, Sina Rashedi, Mohammad-Mahdi Rashidi, Azad Rasul, Zubair Ahmed Ratan, David Laith Rawaf, Salma...
Gesehen am 23.09.2024